Getting under the skin of Polycomb-dependent gene regulation - Blackledge, NP; Klose, RJ (Cold Spring Harbor Laboratory Press, 2021)
The Polycomb repressive system functions through chromatin to regulate gene expression and development. In this issue of Genes & Development, Cohen and colleagues (pp. 354-366) use the developing mouse epidermis as a model system to show that the two central Polycomb repressive complexes, PRC1 and PRC2, have autonomous yet overlapping functions in repressing Polycomb target genes. They show that this cooperation enables the stable repression of nonepidermal transcription factors that would otherwise compromise epidermal cell identity and disrupt normal skin development.